Prevalence Of Acute Kidney Injury In Icu Patients (Journal of Chittagong Medical College Teachers' Association, 2014)
Acute kidney injury (AKI) is common in the intensive care unit (ICU) and is associated with significant morbidity and mortality. This study is aimed to estimate the prevalence of AKI in ICU and assess its relation with different indication of ICU admission and duration of hospital stay. It was a cross sectional study done in the Intensive Care Unit (ICU) of Chittagong Medical College Hospital (CMCH), in the period of six months from 08/07/2012 to 07/01/2013. Hundred consecutive admitted patients in the ICU were taken as study subject and Acute Kidney Injury Network (AKIN) criteria was applied to evaluate the acute kidney injury among the admitted patients. The total number of ICU patients taken in the study were 100. Among them, 62 (62%) patients were male and 38(38%) of the patients were female. Male to female ratio was 1.6:1. 52(52%) came from urban areas and 48(48%) came from rural areas. Regarding the age distribution of total 100 patients age range was 22 to 81 years. The mean + SD was 53.90 – 14.502 years. Among the 100 patients majority were illiterate to primary level educated which were 42(42%). Maximum were in the income group 10,000-20,000 TK/month which is 45(45%). Among all patients housewives were found in 28(28%) cases, followed by retired from service, service holder and businessman in 20(20%), 12(12%) and 16(16%) cases respectively. Regarding analysis of causes of ICU admission respiratory failure was 31% which was highest, then 13% cases were stroke, 12% were septic shock and accidental injury each, postoperative complications were 8%, poisoning was 7%, GBS was 5%, hepatic encephalopathy was 7% and others was 5%. Among the 100 ICU patients, 28(28%) were found to have AKI. Among them, most of the patients (21.4%) of respiratory failure had AKI, next to it was accidental injury (17.8%), postoperative patients(14.2%), septic shock (14.4%), hepatic encephalopathy(10.7%), poisoning (7.2%) and stroke (3.6%). Regarding the renal function tests the mean + SD of blood urea was 46.64 18.19 mg/dl and it was 2.38 + 1.7mg/dl for serum creatinine. Out of 100 patients 57(57%) were ventilated and 43(43%) were not ventilated. Among the 57 ventilated patients 23(40.4%) had AKI and among the 43 non ventilated patients 4(11.6%) had AKI. Distribution was statistically significant (p10 days(n=20) had AKI 30% of patients. Distribution of the AKI according to different duration of hospital stay was statistically significant (p